FACTORS RESPONSIBLE FOR INFLUENCING THE ADVERSE CHILD SEX RATIO: A STUDY ON BIRBHUM DISTRICT OF WEST BENGAL (International Journal of Food and Nutritional Sciences, 2022)
Indian are witnessing a changing pattern of child sex ratio which is a serious problem with severe socio economic, demographic, and cultural consequences. In the last decade, the drastic decline in child sex ratio found to be an important issue which make a grave concern in rural Indian context especially some of the rural districts of West Bengal including Birbhum. The researcher tried to examine the ground realities and demographic scenario of Birbhum district where gender inequality is a serious problem in fabric of the society. This paper has mainly dealt with subject related to character of child sex ratio whether it is deteriorated or improved, considering various socio-economic factors which are regarded as important determinants of different gender preferences in the Birbhum district of West Bengal. In spite of higher mortality predominance for male child, the female child was having a decrease ratio during (0-6) years. That is why the study has revealed special attention on age of the respondents of schedule caste, schedule tribe, Muslim and other communities specifying age at marriage, numbers of children, structure of houses, income, education, job pattern, women's status for studying the nature of child sex ratio. It was observed that skewed in girl child population leads to serious demographic imbalance and adverse social consequences. Accordingly, the researchers have taken an effort to examine the plight child sex ratio, its actual causes and significance in society with the help of worthy methodology and correct field data.